Design of Arduino Uno-Based Automatic Object Sorter Belt Conveyor System Using Ultrasonic Sensors - Sinta Restuasih; Adhes Gamayel; Rano Agustino (Jakarta Global University, 2022)
Belt conveyor is a fairly simple equipment used to transport load units or bulk materials with a large capacity, the tool consists of belts that are resistant to the transport of solid objects. The sabuk used in this Belt Conveyor is made from various types of materials, for example from rubber, plastic, leather or metal which depends on the type and nature of the material to be transported. The testing process of this tool starts by turning on the Conveyor Belt, the rotation on the Conveyor Belt is constant at a speed of 3.1 m / min and there is no speed setting, the speed of the Conveyor Belt can be known using the Tachometer tool and can be calculated manually using the formula v = s / t where v = speed, s = distance and t = time. When the object is attached to the Conveyor Belt the object will run and pass through the Ultrasonic sensor, when the position of the object is directly under the sensor, the sensor will detect the object based on the height or distance between the sensor and the object, so that Arduino Uno can carry out the work process of the object falls into category A, B or C.